Ratzinger's faith : the theology of Pope Benedict XVI - Rowland, Tracey, 1963- (Oxford University Press, 2008)
This volume situates the thought of Benedict XVI within the intellectual history and academic circles of his time, exploring topics such as the interpretations of the Second Vatican Council, Benedict's relations with other important scholars and theologians, and his attitudes on moral and political theology, western culture, the structure of the Catholic Church, liturgy, and love. It is a common observation that Pope Benedict has been influenced by the thought of St. Augustine in contrast to many of his predecessors in the papacy who were much more strongly influenced by St. Thomas Aquinas. This work therefore addresses the topic of in what way Benedict is an Augustinian. The volume also includes a bibliography arranged thematically for those who want to explore his thought more deeply in a particular area. --From publisher's description.